Real-time monitoring of enzyme-assisted animal protein hydrolysis by NMR spectroscopy – An NMR reactomics concept. (September 2018) - Sundekilde, Ulrik K.; Jarno, Lise; Eggers, Nina; Bertram, Hanne Christine
Abstract: This study presents an application of proton ( 1 H) NMR spectroscopy for monitoring of enzyme-assisted hydrolysis of muscle protein under both at-line and real-time conditions. Measurements were carried out on sample material >1 g, and two different enzymes (alcalase and papain) were examined. The real-time monitoring of reactions was carried out directly in the NMR spectrometer, and the technique enabled the dynamic and quantitative detection of a total of 40 metabolites. The approach enabled to follow time evolution and kinetic modelling allowed extraction of kinetic parameters; a was calculated to 0.051 min −1 and 0.029 min −1 for alcalase and papain, respectively, revealing a higher hydrolysis velocity for alcalase than papain. The study demonstrates that NMR spectroscopy is an excellent analytical platform for real-time monitoring of the major metabolite composition changes occurring during an enzymatic hydrolysis. Industrial relevance: Protein hydrolysis is a commonly applied technology in food industry and the presented NMR methodology for kinetic studies of metabolite generation during a hydrolysis process would be applicable for testing and optimization of different raw materials and processing conditions. Highlights: NMR spectroscopy enabled real-time monitoring of protein hydrolysis. Evolution in formation of several free amino acids and flavor precursors was followed. Different dynamics was demonstrated for alcalase and papain enzymes.